Variation in Seed and Seedling Characteristics of Acacia Mangium Willd and A. Auriculiformis A. Cunn. Ex Benth - Hegde, Ramakrishna; Varghese, Mohan; Padmini, S.; Jayaraj, R. S. C. (Indian Forester, 2000)
Acacia mangium and A. auriculiformis are two species of Australian Acacias widely planted as exotics in humid tropical climates. Early introductions of A. auriculiformis to India resulted a land race of poor form. New seedlots of both the species were obtained from native collections of Australia and Papua New Guinea as well as from established Seedling Seed Orchards. These collections were compared with earlier introductions for seed and seedling characteristics and early performance in the field A. auriculiformis had larger and heavier seed and more seedling biomass than A. mangium but the species did not differ in the shape of seed. The Oriomo seedlots ofPNG are reported to perform well in moist areas and the same trend was seen in early growth performance in the present location which receives an annual rainfall of 1500mm. The study has to be continued to identify suitable seedlots for the region.